Prospects of Commercial Date Plum Cultivation in the Environmental Settings of Bangladesh - Khan, MNH; Hassan, MR (Journal of Environmental Science and Natural Resources, 2016)
Agriculture is the single largest producing sector of the economy in Bangladesh. It has a big opportunity to cultivate commercial varieties of Date in the agriculture sector where rice, potato, pulses, wheat etc. are the principal food crops. The present study was conducted to find out the prospects of commercial Date cultivation in the environment of Bangladesh. Date palms are distributed between 10 °N and 39 °N latitude in the northern hemisphere. Date palms require an arid climate with an average temperature between 25°C to 32°C and a sufficient water supply. The environment of Bangladesh complies with the climatic factors in the various date growing areas in the world. J. Environ. Sci. & Natural Resources, 9(1): 63-66 2016